Pengaruh Pengetahuan Perpajakan dan Ketegasan Penerapan Sanksi Terhadap Peningkatan Kepatuhan Pajak Individu: Studi Kasus Pada KPP Pratama Serpong 2020-2024 - Syahriel, Muhammad; Kurniawati, Desi (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
Tax is the main source of state revenue used to finance national development. The level of compliance among individual taxpayers (WPOP) in Indonesia remains an issue that requires special attention. This study aims to analyze the influence of tax knowledge and the strict enforcement of sanctions on improving individual tax compliance. This research is quantitative in nature, employing an associative method. The population consists of individual taxpayers registered at KPP Pratama Serpong, with a sample of 100 respondents determined using Slovin’s formula. Primary data were collected through questionnaires with a Likert scale. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with SmartPLS 4 software. The results show that: (1) tax knowledge has a positive and significant effect on individual tax compliance; (2) strict enforcement of sanctions has a positive and significant effect on individual tax compliance; (3) simultaneously, tax knowledge and strict enforcement of sanctions explain 47.3% of the variation in tax compliance (R² = 0.473). In conclusion, the higher the level of tax understanding and the stricter the enforcement of sanctions, the greater the increase in individual taxpayer compliance. This study is expected to contribute to the Directorate General of Taxes in improving education and law enforcement strategies, as well as serving as a reference for future research.